A lithium-sodium system oxide ceramic film, a preparation method and application thereof
Patent Information
- Application Number
- CN202610925748.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-20
AI Technical Summary
然而锂钠铝酸盐体系陶瓷薄膜因锂和钠饱和蒸气压高、活性强,非常难以制备和控制产品质量,虽然这些物质具有优异的性能,其难以有效合成的问题给其应用带来了巨大的挑战
[0017]本发明所制备的锂钠体系氧化物陶瓷薄膜稳定,包含非晶态、碳酸钠、铝酸钠、铝酸锂、氧化铝及beta氧化铝等多种相,可用于催化加工、核材料、陶瓷刀具、能源电池诸多领域。且工艺成本可控,薄膜沉积速率极快,最高达到100微米每小时以上。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic preparation technology, specifically relating to a lithium-sodium system oxide ceramic thin film, its preparation method and application. Background Technology
[0002] Lithium-sodium aluminate ceramics include alumina, sodium carbonate, sodium aluminate, lithium aluminate, beta alumina, and their amorphous phases. Thin films of these materials are commonly used in catalytic processing, tool strengthening, light-emitting devices (such as LEDs and OLEDs), key nuclear materials, and energy batteries, among many other fields. However, due to the high saturated vapor pressures and strong reactivity of lithium and sodium, lithium-sodium aluminate ceramic thin films are extremely difficult to prepare and control in terms of product quality. Although these materials possess excellent properties, the difficulty in their effective synthesis poses a significant challenge to their applications. Summary of the Invention
[0003] To address the shortcomings of existing technologies, this invention provides a lithium-sodium aluminate system oxide ceramic thin film, its preparation method, and its applications. This invention successfully synthesizes various lithium-sodium aluminate system ceramic thin films by pretreating precursor raw materials and adopting appropriate process conditions. Furthermore, it achieves deposition rates exceeding 100 μm / h, significantly improving production efficiency.
[0004] The technical solution provided by this invention is as follows: A method for preparing a lithium-sodium system oxide ceramic thin film includes the following steps: 1) Sodium source, lithium source and aluminum source were respectively subjected to liquid phase grinding to obtain sodium precursor, lithium precursor and aluminum precursor respectively; 2) Using the precursors obtained in step 1) as raw materials, lithium sodium system oxide ceramic thin films are prepared on the reaction substrate by constant pressure chemical vapor deposition.
[0005] Specifically, in step 1): The sodium source is Na(tmhd) (tmhd = 2,2,6,6-tetramethyl-3,5-heptanedione) or Na(dpm); The lithium source is lithium oxalate or Li (dpm); The aluminum source is 2,4-aluminum acetylacetonate Al(acac)3 or triisobutylaluminum.
[0006] Specifically, in step 1): The solvent used in the grinding process is acetone or butyraldehyde; The grinding time is 10-20 minutes.
[0007] Specifically, step 2) includes the following steps: a) Heat each precursor; b) Heat the reaction substrate; c) Vacuum pumps are used to vaporize each precursor, and argon carrier gas is used to send the vaporized liquid precursor into the reaction zone of the reaction equipment, while oxygen is supplied at the same time. d) Under constant pressure conditions, chemical vapor deposition was performed to obtain lithium-sodium system oxide ceramic thin films; The raw materials used have the following molar ratios: Li to Al is 0-2.0 and the ratio is not zero; Na to Al is 1.5.
[0008] The above technical solution can overcome the deposition problem caused by the high saturated vapor pressure and strong activity of lithium and sodium.
[0009] Specifically, in step a): Heat the sodium precursor to 200-290℃; The lithium precursor is heated to 400-450℃; The aluminum precursor is heated to 220-320℃.
[0010] The above technical solution can reduce the temperature of the gasification precursor during equipment and pipeline transportation, and reduce the loss caused by the chemical reaction of raw materials in the gaseous state.
[0011] Specifically, in step b): the reaction substrate material is aluminum nitride, and the reaction substrate is heated to the range of 300°C to 1100°C.
[0012] Specifically, in step c): The flow rate of the sodium precursor gas stream is 8.0 × 10⁻⁶. -7 m 3 s -1 ; The flow rate of the lithium precursor gas stream is 8.0 × 10⁻⁶. -7 m 3 s -1 ; The flow velocity of the aluminum precursor airflow is 6.0 × 10⁻⁶. -7 m 3 s -1 ; The flow rate of argon gas is 6.0-8.0 × 10⁻⁶. -7 m 3 s -1 ; The oxygen flow rate is 2.0 × 10⁻⁶. -6 m 3 s -1 .
[0013] Specifically, in step d): the pressure is a fixed value between 780-820 Pa, preferably 800 Pa; maintain a stable pressure for 1.5-2.5 minutes; and the deposition time is 60-600 s.
[0014] Specifically, in step d): the deposition rate is greater than or equal to 100 micrometers per hour.
[0015] The present invention also provides lithium-sodium system oxide ceramic thin films prepared by the above preparation method.
[0016] This invention also provides applications of lithium-sodium system oxide ceramic thin films as multifunctional materials for use in batteries, microwaves, sensing, catalysis, etc.
[0017] The lithium-sodium system oxide ceramic thin films prepared by this invention are stable and contain multiple phases, including amorphous, sodium carbonate, sodium aluminate, lithium aluminate, alumina, and beta-alumina. They can be used in various fields such as catalytic processing, nuclear materials, ceramic cutting tools, and energy batteries. Furthermore, the process cost is controllable, and the film deposition rate is extremely fast, reaching over 100 micrometers per hour. Attached Figure Description
[0018] Figure 1 This is a diagram showing the formation conditions of various phases of lithium-sodium system oxide ceramic thin films.
[0019] Figure 2 This is the xrd phase identification diagram of the embodiment.
[0020] Figure 3 This is a SEM microstructure image of an embodiment.
[0021] Figure 4 This is the xrd phase identification diagram of the embodiment.
[0022] Figure 5 This is a SEM microstructure image of an embodiment.
[0023] Figure 6 This is a graph showing the trend of thin film deposition rate as a function of temperature.
[0024] Figure 7 This is a photograph of a lithium-sodium system oxide ceramic thin film. Detailed Implementation
[0025] The principles and features of the present invention are described below. The embodiments given are only for explaining the present invention and are not intended to limit the scope of the present invention.
[0026] Unless otherwise specified, the test methods used in the embodiments are conventional methods; unless otherwise specified, the materials and reagents used are commercially available.
[0027] Example 1 The raw materials Na(tmhd), lithium oxalate, and Al(acac)3 were subjected to liquid-phase pretreatment. The Na(tmhd), lithium oxalate, and Al(acac)3 powders were each subjected to a single liquid-phase milling process. Acetone (20 ml) was used as the solvent during milling, and after milling for 15 minutes, Na(tmhd), lithium oxalate, and Al(acac)3 precursors were obtained. Constant-pressure chemical vapor deposition was then performed. The obtained Na(tmhd), lithium oxalate, and Al(acac)3 precursors were placed in a heating vessel, and the liquid Na(dpm) was heated to 250 °C. o C, The heating temperature of lithium oxalate solvent is 400°C. o The heating temperature of C, Al(acac)3 is 280°C. o C. After heating for 3 minutes, turn on the vacuum pump and adjust the temperature of the reaction substrate (aluminum nitride) to 1163 K according to the corresponding conditions. Then, use argon as a carrier gas to send the vaporized liquid precursor into the reaction zone of the equipment, while simultaneously opening the oxygen supply valve. Adjust the chamber pressure to a constant 800 Pa and maintain the stable pressure for 2 minutes, with a deposition time of 145 s. Completing this step yields a crystalline lithium sodium aluminate ceramic film with a thickness of 2.01 μm. The Li / Al molar ratio of the raw materials consumed is controlled at 0.1; the Na / Al molar ratio is controlled at a fixed value of 1.5. (XRD phase identification diagram is shown below.) Figure 2 Part a, SEM microstructure as follows Figure 3 Part a (surface), d (cross section)).
[0028] physical objects Figure 7 The image shown is a physical photograph of a lithium-sodium system oxide ceramic thin film.
[0029] Example 2 The raw materials Na(tmhd), lithium oxalate, and Al(acac)3 were subjected to liquid-phase pretreatment. The Na(tmhd), lithium oxalate, and Al(acac)3 powders were each subjected to a single liquid-phase milling process. Acetone (20 ml) was used as the solvent during milling, and after milling for 15 minutes, Na(tmhd), lithium oxalate, and Al(acac)3 precursors were obtained. Constant-pressure chemical vapor deposition was then performed. The obtained Na(tmhd), lithium oxalate, and Al(acac)3 precursors were placed in a heating vessel, and the liquid Na(dpm) was heated to 250 °C. o C, The heating temperature of lithium oxalate solvent is 410°C. o C, Al(acac)3 is heated to 280°C. oC. After heating for 3 minutes, turn on the vacuum pump and adjust the temperature of the reaction substrate (aluminum nitride) to 1165 K according to the corresponding conditions. Then, use argon as a carrier gas to send the vaporized liquid precursor into the reaction zone of the equipment, while simultaneously opening the oxygen supply valve. Adjust the chamber pressure to a constant 800 Pa and maintain the stable pressure for 2 minutes, with a deposition time of 125 s. Completing this step yields a crystalline lithium sodium aluminate ceramic film with a thickness of 1.92 μm. The Li / Al molar ratio of the raw materials consumed is controlled at 0.2; the Na / Al molar ratio is controlled at a fixed value of 1.5. (XRD phase identification diagram is shown below.) Figure 2 Part b, SEM microstructure as follows Figure 3 Part b (surface) and part e (cross section)).
[0030] Example 3 The raw materials Na(tmhd), lithium oxalate, and Al(acac)3 were subjected to liquid-phase pretreatment. The Na(tmhd), lithium oxalate, and Al(acac)3 powders were each subjected to a single liquid-phase milling process. Acetone (20 ml) was used as the solvent during milling, and after milling for 15 minutes, Na(tmhd), lithium oxalate, and Al(acac)3 precursors were obtained. Constant-pressure chemical vapor deposition was then performed. The obtained Na(tmhd), lithium oxalate, and Al(acac)3 precursors were placed in a heating vessel, and the liquid Na(dpm) was heated to 250 °C. o C, The heating temperature of lithium oxalate solvent is 440°C. o C, Al(acac)3 is heated to 280°C. o C. After heating for 3 minutes, turn on the vacuum pump and adjust the temperature of the reaction substrate (aluminum nitride) to 1160 K according to the corresponding conditions. Then, use argon as a carrier gas to send the vaporized liquid precursor into the reaction zone of the equipment, while simultaneously opening the oxygen supply valve. Adjust the chamber pressure to a constant 800 Pa and maintain the stable pressure for 2 minutes, with a deposition time of 115 s. Completing this step yields a crystalline lithium sodium aluminate ceramic film with a thickness of 2.11 μm. The Li / Al molar ratio of the raw materials consumed is controlled at 1.0; the Na / Al molar ratio is controlled at a fixed value of 1.5. (XRD phase identification diagram is shown below.) Figure 2 Part c, SEM microstructure as follows Figure 3 Part c (surface) and part f (cross section)).
[0031] Example 4 The raw materials Na(tmhd), lithium oxalate, and Al(acac)3 were subjected to liquid-phase pretreatment. The Na(tmhd), lithium oxalate, and Al(acac)3 powders were each subjected to a single liquid-phase milling process. Acetone (20 ml) was used as the solvent during milling, and after milling for 15 minutes, Na(tmhd), lithium oxalate, and Al(acac)3 precursors were obtained. Constant-pressure chemical vapor deposition was then performed. The obtained Na(tmhd), lithium oxalate, and Al(acac)3 precursors were placed in a heating vessel, and the liquid Na(dpm) was heated to 250 °C. o C, The heating temperature of lithium oxalate solvent is 400°C. o The heating temperature of C, Al(acac)3 is 280°C. o C. After heating for 3 minutes, turn on the vacuum pump and adjust the temperature of the reaction substrate (aluminum nitride) to 910 K according to the corresponding conditions. Then, use argon as a carrier gas to send the vaporized liquid precursor into the reaction zone of the equipment, while simultaneously opening the oxygen supply valve. Adjust the chamber pressure to a constant 800 Pa and maintain the stable pressure for 2 minutes, with a deposition time of 155 s. Completing this step yields a crystalline lithium sodium aluminate ceramic film with a thickness of 6.13 mm. The Li / Al molar ratio of the raw materials is controlled at 0.1; the Na / Al molar ratio is controlled at a fixed value of 1.5. (XRD phase identification diagram is shown below.) Figure 4 Part a, SEM microstructure as follows Figure 5 Part a (surface) and part d (cross section)).
[0032] Example 5 The raw materials Na(tmhd), lithium oxalate, and Al(acac)3 were subjected to liquid-phase pretreatment. The Na(tmhd), lithium oxalate, and Al(acac)3 powders were each subjected to a single liquid-phase milling process. Acetone (20 ml) was used as the solvent during milling, and after milling for 15 minutes, Na(tmhd), lithium oxalate, and Al(acac)3 precursors were obtained. Constant-pressure chemical vapor deposition was then performed. The obtained Na(tmhd), lithium oxalate, and Al(acac)3 precursors were placed in a heating vessel, and the liquid Na(dpm) was heated to 250 °C. o C, The heating temperature of lithium oxalate solvent is 400°C. o The heating temperature of C, Al(acac)3 is 280°C. oC. After heating for 3 minutes, turn on the vacuum pump and adjust the temperature of the reaction substrate (aluminum nitride) to 1135 K according to the corresponding conditions. Then, use argon as a carrier gas to send the vaporized liquid precursor into the reaction zone of the equipment, while simultaneously opening the oxygen supply valve. Adjust the chamber pressure to a constant 800 Pa and maintain the stable pressure for 2 minutes, with a deposition time of 315 s. Completing this step yields a crystalline lithium sodium aluminate ceramic film with a thickness of 5.56 mm. The Li / Al molar ratio of the raw materials is controlled at 0.1; the Na / Al molar ratio is controlled at a fixed value of 1.5. (XRD phase identification diagram is shown below.) Figure 4 Part b, SEM microstructure as follows Figure 5 Part b (surface) and part e (cross section)).
[0033] Example 6 The raw materials Na(tmhd), lithium oxalate, and Al(acac)3 were subjected to liquid-phase pretreatment. The Na(tmhd), lithium oxalate, and Al(acac)3 powders were each subjected to a single liquid-phase milling process. Acetone (20 ml) was used as the solvent during milling, and after milling for 15 minutes, Na(tmhd), lithium oxalate, and Al(acac)3 precursors were obtained. Constant-pressure chemical vapor deposition was then performed. The obtained Na(tmhd), lithium oxalate, and Al(acac)3 precursors were placed in a heating vessel, and the liquid Na(dpm) was heated to 250 °C. o C, The heating temperature of lithium oxalate solvent is 400°C. o The heating temperature of C, Al(acac)3 is 280°C. o C. After heating for 3 minutes, turn on the vacuum pump and adjust the temperature of the reaction substrate (aluminum nitride) to 1175 K according to the corresponding conditions. Then, use argon as a carrier gas to send the vaporized liquid precursor into the reaction zone of the equipment, while simultaneously opening the oxygen supply valve. Adjust the chamber pressure to a constant 800 Pa and maintain the stable pressure for 2 minutes, with a deposition time of 290 s. Completing this step yields a crystalline lithium sodium aluminate ceramic film with a thickness of 4.02 mm. The Li / Al molar ratio of the raw materials is controlled at 0.1; the Na / Al molar ratio is controlled at a fixed value of 1.5. (XRD phase identification diagram is shown below.) Figure 4 Part c, SEM microstructure as follows Figure 5 Part c (surface) and part f (cross section)).
[0034] Comparative Example 1 Referring to the embodiments, the difference lies in that the deposition temperature is increased or decreased, and the heating temperature of lithium oxalate is adjusted, thereby controlling the Li / Al ratio and obtaining different phases of lithium sodium oxide ceramics. For example, increasing the Li / Al ratio easily yields Li-containing phases, such as LiAl5O8 and LiAlO2, which are beneficial for use as fluorescent and piezoelectric materials. Increasing the synthesis temperature easily yields BETA phases containing very small amounts of Li and Na, as well as pure alumina, which are beneficial for use as rechargeable battery separators and ceramic reinforcing coatings. When the temperature is lower and the amount of Li and Na is higher, sodium carbonate is easily obtained, which is related to the incomplete reaction of the raw materials.
[0035] The materials in Examples 1-3 are suitable as battery electrolyte materials because they have lithium and sodium ion conductivity.
[0036] The materials in Examples 4-6, LiAlO2, are suitable as dielectric materials and deuterium inoculum materials because of its microwave absorption and stability.
[0037] like Figure 6 The figure shown is a graph showing the trend of thin film deposition rate as a function of temperature.
[0038] like Figure 1 The diagram shown illustrates the formation conditions of various phases of oxide ceramic thin films in a lithium-sodium system.
[0039] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a lithium-sodium system oxide ceramic thin film, characterized in that, Includes the following steps: 1) Sodium source, lithium source and aluminum source were respectively subjected to liquid phase grinding to obtain sodium precursor, lithium precursor and aluminum precursor respectively; 2) Using the precursors obtained in step 1) as raw materials, lithium sodium system oxide ceramic thin films are prepared on the reaction substrate by constant pressure chemical vapor deposition.
2. The method for preparing lithium-sodium system oxide ceramic thin films according to claim 1, characterized in that, In step 1): The sodium source is Na(tmhd) or Na(dpm); The lithium source is lithium oxalate or Li (dpm); The aluminum source is aluminum 2,4-acetylacetonate or triisobutylaluminum.
3. The method for preparing lithium-sodium system oxide ceramic thin films according to claim 1, characterized in that, In step 1): The solvent used in the liquid phase grinding process is acetone or butyraldehyde; The liquid phase grinding time is 10-20 minutes.
4. The method for preparing lithium-sodium system oxide ceramic thin films according to claim 1, characterized in that, Step 2) specifically includes the following steps: a) Heat each precursor; b) Heat the reaction substrate; c) Vacuum pumps are used to vaporize each precursor, and argon carrier gas is used to send the vaporized liquid precursor into the reaction zone of the reaction equipment, while oxygen is supplied at the same time. d) Under constant pressure conditions, chemical vapor deposition was performed to obtain lithium-sodium system oxide ceramic thin films; The raw materials used have the following molar ratios: Li to Al is 0-2.0; Na to Al is 1.
5.
5. The method for preparing lithium-sodium system oxide ceramic thin films according to claim 4, characterized in that, In step a): Heat the sodium precursor to 200-290℃; The lithium precursor is heated to 400-450℃; The aluminum precursor is heated to 220-320℃.
6. The method for preparing lithium-sodium system oxide ceramic thin films according to claim 4, characterized in that, In step b): the reaction substrate material is aluminum nitride, and the reaction substrate is heated to the range of 300°C to 1100°C.
7. The method for preparing lithium-sodium system oxide ceramic thin films according to claim 4, characterized in that, In step c): The flow rate of the sodium precursor gas stream is 8.0 × 10⁻⁶. -7 m 3 s -1 ; The flow rate of the lithium precursor gas stream is 8.0 × 10⁻⁶. -7 m 3 s -1 ; The flow velocity of the aluminum precursor airflow is 6.0 × 10⁻⁶. -7 m 3 s -1 ; The flow rate of argon gas is (6.0-8.0) × 10⁻⁶. -7 m 3 s -1 ; The oxygen flow rate is 2.0 × 10⁻⁶. -6 m 3 s -1 .
8. The method for preparing lithium-sodium system oxide ceramic thin films according to claim 4, characterized in that, In step d): The constant pressure is a fixed value between 780-820 Pa; maintain a stable pressure for 1.5-2.5 minutes; Deposition time: 60-600 s; The deposition rate is greater than or equal to 100 micrometers per hour.
9. A lithium-sodium system oxide ceramic thin film prepared by the preparation method according to any one of claims 1 to 8.
10. An application of the lithium-sodium system oxide ceramic thin film according to claim 9, characterized in that: It can be used as a battery material, microwave material, sensing material, or catalytic material.